Rethinking Tax Systems for Sustainable Development Goals - Sugihyanty, Eneng; Safri; Faisal, Ahmad (Yayasan Sinergi Kawula Muda, 2024)
Taxation plays a pivotal role in advancing sustainable development goals (SDGs), yet its implementation faces several systemic challenges. This narrative review aims to explore the effectiveness of tax policies in supporting SDGs through the lenses of environmental taxation, fiscal incentives, progressive tax reforms, and digital transformation. A qualitative review method was employed to synthesize findings from recent empirical and comparative studies, focusing on the interaction between taxation mechanisms and sustainability outcomes. The results highlight that environmental taxes effectively reduce carbon emissions and promote energy efficiency, while fiscal incentives drive investments in renewable energy by alleviating financial constraints. Progressive taxation contributes to income redistribution and social justice, particularly in low- and middle-income countries. Furthermore, institutional quality and good governance are crucial in enhancing the success of fiscal strategies, with countries exhibiting stronger institutions achieving higher efficiency and compliance. The digitalization of tax systems, including AI-enabled tax education, further improves transparency and public trust. Despite these benefits, challenges such as tax system complexity, coordination failures, and data limitations hinder the optimal realization of taxation’s potential. Thus, the study recommends integrated policy reforms, enhanced public engagement, and further interdisciplinary research to strengthen tax systems as instruments for sustainable development. These insights provide a strategic foundation for policymakers aiming to align fiscal systems with the global SDG agenda.